State ownership and corporate leverage around the world - De Haas, Ralph; Guriev, Sergei; Stepanov, Alexander (Journal of Corporate Finance, 2025)
Does state ownership hinder or help firms access credit? We use data on almost 4 million firms in 89 countries to study the relationship between state ownership and corporate leverage. Controlling for country-sector-year fixed effects and conventional firm-level determinants of leverage, we show that state ownership is robustly and negatively related to corporate leverage. This relationship holds across most of the firm-size distribution – with the important exception of the largest companies – and is stronger in countries with weak political and legal institutions. A panel data analysis of privatized firms and a comparison of privatized with matched control firms yield similar qualitative and quantitative effects of state ownership on leverage.